Sulfur Metabolism of Hydrogenovibrio thermophilus Strain S5 and Its Adaptations to Deep-Sea Hydrothermal Vent Environment - Jiang, Lijing; Lyu, Jie; Shao, Zongze (Frontiers in Microbiology, 2017)
Hydrogenovibrio bacteria are ubiquitous in global deep-sea hydrothermal vents. However, their adaptations enabling survival in these harsh environments are not well understood. In this study, we characterized the physiology and metabolic mechanisms of Hydrogenovibrio thermophilus strain S5, which was first isolated from an active hydrothermal vent chimney on the Southwest Indian Ridge. Physiological characterizations showed that it is a microaerobic chemolithomixotroph that can utilize sulfide, thiosulfate, elemental sulfur, tetrathionate, thiocyanate or hydrogen as energy sources and molecular oxygen as the sole electron acceptor. During thiosulfate oxidation, the strain produced extracellular sulfur globules 0.7–6.0 µm in diameter that were mainly composed of elemental sulfur and carbon. Some organic substrates including amino acids, tryptone, yeast extract, casamino acids, casein, acetate, formate, citrate, propionate, tartrate, succinate, glucose and fructose can also serve as carbon sources, but growth is weaker than under CO2 conditions, indicating that strain S5 prefers to be chemolithoautotrophic. None of the tested organic carbons could function as energy sources. Growth tests under various conditions confirmed its adaption to a mesophilic mixing zone of hydrothermal vents in which vent fluid was mixed with cold seawater, preferring moderate temperatures (optimal 37°C), alkaline pH (optimal pH 8.0), microaerobic conditions (optimal 4% O2), and reduced sulfur compounds (e.g. sulfide, optimal 100 μM). Comparative genomics showed that strain S5 possesses more complex sulfur metabolism systems than other members of genus Hydrogenovibrio. The genes encoding the intracellular sulfur oxidation protein (DsrEF) and assimilatory sulfate reduction were first reported in the genus Hydrogenovibrio. In summary, the versatility in energy and carbon sources, and unique physiological properties of this bacterium have facilitated its adaptation to deep-sea hydrothermal vent environments.